Assessment of genetically modified maize DP4114 × MON 89034 × MON 87411 × DAS‐40278‐9 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA GMO‐NL‐2020‐171). (9th November 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Genetically modified maize DP4114 × MON 89034 × MON 87411 × DAS‐40278‐9 was developed by crossing to combine four single events: DP4114, MON 89034, MON 87411 and DAS‐40278‐9. The GMO Panel previously assessed the four single maize events and two of the subcombinations and did not identify safety concerns. No new data on the single maize events or the assessed subcombinations were identified that could lead to modification of the original conclusions on their safety. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single maize events and of the newly expressed proteins in the four‐event stack maize does not give rise to food and feed safety and nutritional concerns. Therefore, no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable four‐event stack maize grains into the environment, this would not raise environmental safety concerns. The GMO Panel assessed the likelihood of interactions among the single events in eight of the maize subcombinations not previously assessed and concludes that these are expected to be as safe as the single events, the previously assessed subcombinations and the four‐event stack maize. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize DP4114 × MON 89034 × MON 87411 × DAS‐40278‐9. Post‐market monitoring of food/feed is not considered necessary. The GMO Panel concludes that the four‐event stack maize and its subcombinations are as safe as its non‐GM comparator and the tested non‐GM maize varieties with respect to potential effects on human and animal health and the environment.